Foundation and development of the department of surgical dentistry and maxillofacial surgery of Bukovinian State Medical University - Alla Halahdina; Lalita Gerasym (Kazimierz Wielki University, 2019)
The article highlights the foundation and development of the department of surgical dentistry and maxillofacial surgery of Bukovinian State Medical University.